Differential impacts of brassicaceous and nonbrassicaceous oilseed meals on soil bacterial and fungal communities. Issue 3 (6th November 2012) - Hollister, Emily B.; Hu, Ping; Wang, Autumn S.; Hons, Frank M.; Gentry, Terry J.
Abstract Demand for alternative fuels has sparked renewed interest in the production of biodiesel from oil‐rich seeds. Oilseed meals are a byproduct of this process, and given their relatively high nutrient content, land application represents a potential value‐added use. In this microcosm‐based study, soil microbial community responses to amendments of a glucosinolate‐containing brassicaceous oilseed meal (Brassica juncea, mustard), a non‐glucosinolate‐containing, nonbrassicaceous oilseed meal (Linum usitatissimum, flax), and a nonoilseed biomass (Sorghum bicolor) were characterized using a 28‐day time series of replicated 16S rRNA gene and fungal ITS gene sequence libraries. We hypothesized that biomass type and glucosinolate content would alter community composition but that effects would diminish over time. Distinct separation occurred by amendment type, with mustard inducing large increases in the abundance of bacterial taxa associated with fungal disease suppression (e.g. Bacillus, Pseudomonas, and Streptomyces spp.). Dramatic shifts were seen among the fungi, too, with phylotype richness decreasing by > 60% following mustard addition. Changes in bacterial and fungal community composition were rapid, and distinct community types persisted throughout the study. Oilseed amendment, and mustard in particular, has the potential to alter soil microbial community structure substantially, and such changes are likely to be important in the context of ecosystem health.